A Commentary on the Potential Use of Oral Microbiome in Prediction, Diagnosis or Prognostics of a Distant Pathology - Egija Zaura (MDPI AG, 2022)
In health, the oral microbiome is in balance with its host. If this balance is lost, this symbiosis is replaced by dysbiotic microbial communities, which are thought to affect the rest of the body either directly or via metabolites or pro-inflammatory molecules. The association of oral microbiome with general health has led to attempts to use oral microbial biomarkers for the prediction, diagnosis or prognosis of distant pathologies such as colorectal carcinoma or pancreatic cancer. These attempts however have no chance to succeed if the complexity of the oral ecosystem and the interplay of environmental, behavioral and biological factors is not taken into account. Standardized, well-documented oral sample collection procedures together with detailed clinical oral examination and behavioral data are the prerequisites for the successful evaluation of the oral microbiome as a potential biomarker for distant pathologies.